The learning process to become a military leader: born, background and lifelong learning - Díez, Fernando; Martínez-Morán, Pedro C.; Aurrekoetxea-Casaus, Maite (Frontiers in Education, 2023)
This paper analyzes the leadership learning model used by Spanish military commanders from the lifelong learning methodology. The lifelong learning approach consists of three main perspectives: a personal and professional context and how to achieve self-motivation and remain over time; the formal and informal learning sources, and how all this occurs throughout the individual life. Leadership is a fundamental military trait and should be treated as an ongoing process. This study examines how influences the lifelong learning of the Spanish military leaders from the Army, Navy, and Air Force in their leadership style. The methodology resource used is an online Delphi technique through in-depth interviews as well as the Qualitative Data Analysis & Research Software Atlas.it. This research shows that from a lifelong learning perspective, military leadership is built continuously throughout life and is supported by more informal than formal learning systems. The key findings of this research show that the Spanish military commanders’ leadership comes from an informal approach based on the different opportunities given at the workspace, individual job performance, and family support. From the formal system, the career ladder is supported both at the military academy and following regular training. The results show that a lifelong learning framework prepares Spanish military commanders to manage the highly complex environment in which they are involved.